The effect of Return on Assets (ROA) and Earnings per Share (EPS) on stock prices: A study of banking companies listed on the Indonesia Stock Exchange, 2018–2024 - Intan Nurrizky Arnas; Eri Novari; Muhammad Sandi Marta; Sholikul Hadi; Dewi Kurniasar (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to examine the effect of Return on Assets (ROA) and Earnings per Share (EPS) on stock prices of banking companies listed on the Indonesia Stock Exchange during 2018–2024. A quantitative approach with a descriptive-verificative method was employed using secondary data from annual reports, financial statements, and historical stock prices. The sample consisted of 10 banking companies selected through purposive sampling from a population of 47 companies, resulting in 70 company-year observations. The data were analyzed using panel data regression with EViews 12, with the Fixed Effects Model (FEM) selected as the appropriate regression model. Hypotheses were tested using the t-test, F-test, and coefficient of determination (R²) at a 5% significance level. The results indicate that ROA has a positive and significant effect on stock prices, whereas EPS has a negative and significant effect. Simultaneously, ROA and EPS have a significant effect on stock prices. The R-squared value of 0.609592 indicates that ROA and EPS jointly explain 60.9592% of the variation in stock prices, while the remaining 39.0408% is attributable to other factors outside the research model. These findings provide empirical evidence that financial performance information, particularly asset profitability and earnings per share, is relevant to stock price valuation in the banking sector and supports the application of Signaling Theory in explaining investors’ responses to financial information.